Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/pssa.201701023
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric, Piezoelectric and Dielectric Behaviors of CoO‐ and Fe2O3‐Doped BCZT Ceramics

Abstract: This study investigates the effect of CoO and Fe2O3 dopant on phase, microstructure and ferroelectric properties of BCZT ceramics with the formula of Ba0.85Ca0.15Zr0.1(Ti1‐xCox)0.9O3 and Ba0.85Ca0.15Zr0.1(Ti1‐xFex)0.9O3 where x = 0, 0.01, and 0.03. The XRD patterns presented that the pure perovskite phases are observed regardless of the amount of CoO and Fe2O3 added. Rietveld analysis shows that the tetragonal phase is observed in all patterns and the unit cell volume slightly expanded by the CoO addition whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…There are still mixed phases in BCZTM, whereas only the R phase is observed in BCZTF, BCZTC, and BCZTN ceramics . It is expected that ions with radius less than 0.870 Å such as Mn 2+ (0.670 Å), Fe 3+ (0.645 Å), Co 2+ (0.745 Å), and Ni 2+ (0.690 Å) will occupy the B‐site, which may induce contraction of the lattice. In addition, oxygen vacancies caused by charge imbalance promote lattice shrinkage .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are still mixed phases in BCZTM, whereas only the R phase is observed in BCZTF, BCZTC, and BCZTN ceramics . It is expected that ions with radius less than 0.870 Å such as Mn 2+ (0.670 Å), Fe 3+ (0.645 Å), Co 2+ (0.745 Å), and Ni 2+ (0.690 Å) will occupy the B‐site, which may induce contraction of the lattice. In addition, oxygen vacancies caused by charge imbalance promote lattice shrinkage .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Sun et al reported that Mn‐doped BCZT ceramic (0.3 mol%) had excellent ferroelectric ( P r = 15.7 μC/cm 2 , E c = 180 V/mm), dielectric (tan δ = 1.04%), and piezoelectric ( d 33 = 308 pC/N) properties. Jaimeewong et al also observed favorable dielectric ( ε r = 4567) and piezoelectric ( d 33 = 276 pC/N) properties in CoO‐ and Fe 2 O 3 ‐doped BCZT ceramics. In addition, owing to their excellent dielectric energy storage performance, BaTiO 3 ‐based materials are of great value in memory and transformer applications and can also be applied to high‐temperature capacitors and pulsed power …”
Section: Introductionmentioning
confidence: 91%
“…V 2 O 5 was doped with BCZT by Y. Yang et al and solid state method yielded d 33 = 466 pC/N, P r = 7.735 μC/cm 2 , ε r = 3104, and tanδ = 0.03, implying favorable applications for lead-free piezoelectric ceramics [50]. Some other methods like surfactant-assisted solvothermal processing [55,56,57,58,59,60,61,62,63,64,65,66,67,68,69] oxide-mixed method [56], citrate method [51,52,53,54,55,56,57,58], ceramic route [51], mixed oxide (and carbonates) method [70,71,72], spark plasma sintering technique [73], and Pechini polymeric method [74] were also employed.…”
Section: Synthesis Techniques Effects On Dielectric Properties Of mentioning
confidence: 99%
“…Jaimeewong et al investigated the effect cobalt oxide (CoO) and iron oxide (Fe 2 O 3 ) as dopants on dielectric properties of BCZT and found that the BCZT-0.01Co ceramics presented the finest properties, that is, d33 = 276 pC/N and εr= 4567. The Co doped BCZT ceramics could be employed to prepare lead-free materials with striking properties as shown in the Figure 9 [71].…”
Section: Dielectric Properties Of Doped Bcztmentioning
confidence: 99%
See 1 more Smart Citation